2022
DOI: 10.1037/pspi0000370
|View full text |Cite
|
Sign up to set email alerts
|

Status of immigrants’ country of origin and Americans’ assimilation expectations.

Abstract: Building on perspectives on triadic group relations and status hierarchies, we predicted that Americans would be more likely to expect immigrants from a perceived low-status rather than high-status country of origin to assimilate to the U.S. mainstream culture and that ethnocentrism would mediate this effect (N = 2,246). Using 60 countries/areas as targets, Study 1 showed that perceived country status negatively predicted assimilation expectations for immigrants from that country. In Studies 2 through 3, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…The results expand on previous findings (see Williams et al, 2015) that stereotypes associated with ethnic groups across countries to some extent track the stereotypes associated with the ecologies in which these ethnic groups are assumed to predominantly live. Moreover, the recent literature actively uses the concept of status of countries of origin (e.g., Gheorghiu et al, 2022; Kustov, 2019; Zhao & Biernat, 2022) but does not provide a systematic view on the ranking includes mapping countries of origin. Thus, this paper has filled this gap.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results expand on previous findings (see Williams et al, 2015) that stereotypes associated with ethnic groups across countries to some extent track the stereotypes associated with the ecologies in which these ethnic groups are assumed to predominantly live. Moreover, the recent literature actively uses the concept of status of countries of origin (e.g., Gheorghiu et al, 2022; Kustov, 2019; Zhao & Biernat, 2022) but does not provide a systematic view on the ranking includes mapping countries of origin. Thus, this paper has filled this gap.…”
Section: Discussionmentioning
confidence: 99%
“…The details of how these two types of information about group status are combined remain to be understood. For example, Zhao & Biernat (2022) recently discussed that the individual-based/occupation-based status of immigrants could interact with their country-based status to affect assimilation expectations by the host society. Nevertheless, the recent work demonstrated that Spanish host society members prefer immigrants of higher country status over those of lower country status regardless of immigrants’ individual characteristics (Kustov, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… Note. 1.5 generation is used to categorize individuals that arrived in the United States as children, typically before the age of 12 (Zhao & Biernat, 2022); second generation denotes those born in the U.S.…”
Section: Methodsmentioning
confidence: 99%
“…The host group leaves no room for cultural differences among low-status immigrants. A recent study conducted in the United States showed that compared with high-status immigrants, participants were more likely to expect low-status immigrants to abandon their specific culture and assimilate to the United States (Zhao & Biernat, 2022). In other words, immigrants of high social status are allowed to express different acculturation orientations.…”
Section: Worldview Ideologies and Immigrants' Social Statusmentioning
confidence: 99%